An Experimental Investigation on Stabilisation of Clay Soils with Fly-ash Based Geopolymer - Abdullah, Hayder Hasan (Curtin University, 2020)
Geopolymer is a cementitious material that can replace traditional binders in several geotechnical applications, such as soil stabilisation, with the advantages of much lower harmful emissions and energy consumption. The behaviour of geopolymer-treated soil was investigated and practical procedures were developed aiming at examining the suitability of clay for geopolymer treatment and determining the optimum geopolymer quantity for an effective stabilisation. The study is expected to provide a significant contribution to the current soil stabilisation practice.